2007
DOI: 10.1242/jeb.02674
|View full text |Cite
|
Sign up to set email alerts
|

Hair plate mechanoreceptors associated with body segments are not necessary for three-dimensional path integration in desert ants,Cataglyphis fortis

Abstract: consider the (much longer) actual walking trajectory, instead of the base distance, when calculating their homing distance. Surprisingly, neither shaving nor immobilisation of the hair sensillae affected correct path integration, across both uneven terrain (3-D) and level surface. If anything, the ants underestimated homing distance, which may reflect a general, safety-oriented navigation strategy. Animals that had performed the outbound journey with their gaster fixed in a horizontal position underestimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…Obviously, the change in POL pattern accompanying an excursion on sloped path segments is not the major cue on which the perception of slopes is based. Hence, we must further conclude that Cataglyphis relies on some proprioceptive information, even though different manipulations so far could not reveal the crucial ones (Wittlinger et al, 2007b;Seidl and Wehner, 2008 …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Obviously, the change in POL pattern accompanying an excursion on sloped path segments is not the major cue on which the perception of slopes is based. Hence, we must further conclude that Cataglyphis relies on some proprioceptive information, even though different manipulations so far could not reveal the crucial ones (Wittlinger et al, 2007b;Seidl and Wehner, 2008 …”
Section: Discussionmentioning
confidence: 90%
“…As energy expenditure has been ruled out as a cue (Schäfer and Wehner, 1993;Wohlgemuth et al, 2002;Lipp et al, 2005), the most likely hypothesis was that ants use hair fields at various joints to monitor changes in body posture or load distribution (Markl, 1962). However, although Wittlinger et al (Wittlinger et al, 2007b) eliminated or immobilized a series of hair sensors at different joints, these hair fields appeared not to contribute to, or at least were dispensable for, slope perception. An alternative hypothesis was based on the observation that the head posture of ants changes considerably while ants are walking on an ascent or descent (see Introduction) (Seidl and Wehner, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cataglyphis were found to employ odometry during inclined locomotion (Wittlinger et al, 2006;Wohlgemuth et al, 2001), and it has been suggested that both odometry and gravity perception could play a key role in their threedimensional path integration. However, the primary receptors in gravity perception for Formica, the hair fields located on the body joints (Markl, 1962(Markl, , 1974, were not necessary for path integration of Cataglyphis (Wittlinger et al, 2007), neither was the monitoring of the thorax-coxae joint angles. Instead, force sensors such as muscular strain sensors and campaniform sensilla could provide idiothetic cues for three-dimensional path integration (Seidl and Wehner, 2008).…”
Section: Coordination and Navigationmentioning
confidence: 99%
“…To date, it is only clear which parameters are not used in this context. For example, the fields of sensory hairs typically associated with graviception in ants (Markl, 1962) have been excluded as a means of threedimensional orientation through ablation experiments (Wittlinger et al, 2007b). Again, the data from spiders [as described above (review by Barth, 2002)] would suggest leg mechanoreceptors as a possible means of three-dimensional orientation; however, at present this is purely speculative.…”
Section: Distance Cues: Optic Flow and Stride Integrationmentioning
confidence: 99%